Роль реклами у формуванні іміджу загальноуніверситетських кафедр ЗВО - Вовк, Наталія; Гула, Оксана (Видавництво Львівської політехніки, 2019)
The article considers the place of advertising in the image of university colleges of institutions of higher education. The authors develop an information model for the distribution of printing products of the university department and find the advantages of using such products.
Keywords: реклама; студенти; освіта; маркетинг; загальноуніверситетські кафедри